Internal Control System for Cash Receipts in Local Retail: The Case of Matahari Grocery Store - Pradana, Adjie; Haykal, Afrie; Mahendra, Pandu; Fryli, Yosy; Aini, Anahari (PT Global Digital Sains Tekno, 2025)
Purpose: This study aims to evaluate the effectiveness of the cash receipts accounting system at Matahari Grocery Store, a retail business in Surabaya, in supporting financial accuracy, operational efficiency, and the safeguarding of cash assets. Method: A qualitative descriptive approach was employed, incorporating direct observation, semi-structured interviews with the store owner and staff, and document analysis to gain a comprehensive understanding of the store’s accounting practices. Findings: The store utilizes a computerized cash register system that automatically records customer transactions and accommodates multiple payment methods, including cash, debit cards, and QRIS. Although daily cash checks are still performed manually by the owner, the system significantly improves transaction accuracy and efficiency. Internal control mechanisms—such as task segregation, authorization procedures, and the use of numbered receipts—are effectively implemented to reduce errors and prevent fraud. Implication: The findings underscore the importance for small and medium-sized enterprises (SMEs) to integrate technological tools with internal control systems to enhance financial accountability and support informed decision-making. Originality: This research presents a grounded analysis of internal control practices within a local retail setting, offering actionable insights for SMEs seeking to refine their accounting systems. Its originality lies in the detailed exploration of the procedures and the practical relevance of its recommendations.